Prospective study comparing between plate osteosynthesis and antegrade interlocking nailing its functional and radiological outcome in treating humeral shaft fractures - Bhaktharahalli Ramachandra, Harshavardhan; Narayan, Praveen; Chintapalli, Surya Sri Karun; Ram, Pothuri Rishi (International Journal of Research in Orthopaedics, 2023)
Humeral shaft fractures are common injuries making upto 1-3% of all fractures. They are widely treated by conservative methods leading to higher rates of non-union. Henceforth surgeons tend to perform operative procedures to treat them. To statistically analyse and compare the functional and radiological outcome of two treatment modalities of humeral shaft fractures, they are plate osteosyntheis and antegrade intramedullary nailing. A total of 22 patients of humeral shaft fractures were operated by either of two methods 12 in plating (P) group ,10 in nailing (N) group and their radiological outcome was assessed by rate of union, time taken for callus formation etc and their Functional outcome was analysed based on Rodriguez Merchan criteria. The commonest age group of patients operated is 21-40 years (70%) majority being males (70%) and road traffic accident being commonest mode of injury. The plate osteosynthesis group stands superior than nailing group in terms of duration of union (20 weeks), rate, percentage of union (100%), least risk of non-union (0). Statistically significant (p<0.05) improvement in shoulder joint function with minimal complications. The plate osteosynthesis method is the most promising surgical procedure for treating humeral shaft fracture due to negligible rates of non-union and early recovery of motion. Though nailing group has minimal need of soft tissue dissection, preserves fracture biology, decreased operative time and early rehabilitation period it still stands inferior when it comes to complications like rotator cuff injury, shoulder impingement pain and restriction of shoulder movements. Ultimately the post operative quality of life is equally good in both techniques.